University experiences of students and graduates with neurodiversity: tools for creating a specialized mentoring program related to working life - Aguilera Rodríguez, Gerardo; Márquez González, Claudia Verónica; Villaseñor-Cabrera, Teresita J.; Valadez Sierra, María de los Dolores (Frontiers in Education, 2024)
Introduction The term neurodiversity encompasses a range of conditions, including autism, attention deficit and hyperactivity disorder, dyslexia, and dyscalculia. In higher education, students with these conditions often face barriers that hinder their optimal academic performance. These barriers stem from their specific needs and institutional requirements. This situation can also negatively impact their ability to transition into the workforce. Therefore, it is necessary to design strategies that ensure specialized support for this population, guided by the opinions of neurodiverse students. The objective of this study is to identify the needs, difficulties, and tools related to the transition into the workforce, as reported by neurodiverse students and graduates from the bachelor's degree in psychology program, who present some conditions of neurodiversity. Methods For this purpose, a qualitative/phenomenological research was carried out. Results The gathered opinions revealed that the main needs of students include the following: increased awareness and capacity within higher education institutions for timely diagnosis, the implementation of reasonable adjustments for better integration into their activities, provision of supportive environments, the development of strategies to enhance cognitive and emotional aspects, such as planning skills, time management, and emotional regulation skills. Discussion The results of this study are consistent with other studies that emphasize the importance of creating a compassionate pedagogy in educational settings. This involves a greater commitment from educators to address and improve pedagogical practices, provide necessary tools, and develop strategies to help students with neurodiversity conditions throughout their careers. The limitations of this study include the small sample size and restricted depth of the interviews. Therefore, future research should increase the number of participants and explore the interviews in greater depth.